ЎТКИР ПАНКРЕАТИТНИ ТАШХИСЛАШ ВА ЖАРРОҲЛИК ДАВОЛАШДА НУРЛИ ҲАМДА ЭНДОВИЗУАЛ ТЕХНОЛОГИЯЛАРНИНГ САМАРАДОРЛИГИ EFFECTIVENESS OF IMAGING AND ENDOVISUAL TECHNOLOGIES IN THE DIAGNOSIS AND SURGICAL TREATMENT OF ACUTE PANCREATITIS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Acute pancreatitis remains one of the most urgent abdominal emergencies worldwide, characterized by high complication rates, disability, and mortality. The variability of its clinical course and the insufficient clarity of early clinical signs complicate timely diagnosis and selection of optimal treatment tactics. In Uzbekistan, the incidence of acute pancreatitis has increased in recent years, largely attributable to cholelithiasis, dietary changes, and metabolic disorders. In routine practice, diagnostics are often limited to conventional clinical and ultrasound methods, restricting early detection of severe disease forms. Modern imaging technologies — computed tomography (CT) and magnetic resonance imaging (MRI) — alongside endovisual methods, including endoscopic ultrasound and minimally invasive endoscopic interventions, have acquired pivotal importance in diagnosis and treatment planning. However, integrated algorithms combining these modalities in local settings remain insufficiently studied.